Experience with the largest custom-made 48 mm fenestrated atrial septal occluder device and its 4-year follow-up - Kothandam Sivakumar; Gaurav Jain (Wolters Kluwer Medknow Publications, 2023)
Atrial septal defects (ASDs) measuring <38 mm are referred for transcatheter closure. Availability of larger devices up to 46 mm extended the inclusion criteria. An elderly hypertensive male with a 44 mm secundum ASD and coexistent sick sinus syndrome and atrioventricular (AV) nodal block presented with syncope. Balloon interrogation unmasked restrictive left ventricular (LV) physiology. After AV synchronous pacing, balloon-assisted deployment of a custom fenestrated 48 mm Figulla septal occluder (Occlutech Inc., Schaffhausen, Switzerland) prevented a rise of LV end-diastolic pressures beyond 12 mmHg. Echocardiogram and computed tomography after 4 years confirmed a patent fenestration and favorable remodeling. This report of the clinical use of the largest ASD device demonstrated the feasibility of closure of extremely large defects despite a restrictive LV.